2015
DOI: 10.1371/journal.pone.0125267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Adolescent Sexual and Reproductive Health Intervention on Health Service Usage by Young People in Northern Ghana: A Community-Randomised Trial

Abstract: BackgroundWhile many Ghanaian adolescents encounter sexual and reproductive health problems, their usage of services remains low. A social learning intervention, incorporating environment, motivation, education, and self-efficacy to change behaviour, was implemented in a low-income district of northern Ghana to increase adolescent services usage. This study aimed to assess the impact of this intervention on usage of sexual and reproductive health services by young people.MethodsTwenty-six communities were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 59 publications
2
83
0
Order By: Relevance
“…Studies evaluated interventions that targeted three broad groups of health topics: sexual and reproductive health (six studies), communicable diseases (three studies) and non‐communicable diseases (one study). In terms of outcomes, the majority of studies measured healthcare utilisation (six studies) , whilst three studies measured compliance to treatment , and one study measured immunisation uptake (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies evaluated interventions that targeted three broad groups of health topics: sexual and reproductive health (six studies), communicable diseases (three studies) and non‐communicable diseases (one study). In terms of outcomes, the majority of studies measured healthcare utilisation (six studies) , whilst three studies measured compliance to treatment , and one study measured immunisation uptake (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Integrating school-based educational activities, outof-school outreach, community mobilisation, and staff training in youth-friendly service provision was shown to enhance service uptake in Ghana in a formal comparison, with more limited intervention components of staff training or community mobilisation alone. 15 The views of young people themselves about what aspects of service provision are the most important and how these are valued can be ascertained through formal methods, such as discrete choice experiments. 16 In Ntcheu District, a discrete choice experiment carried out in 2012 suggested that the preferred service model was one that assured confidentiality as the first priority, also included HIV testing and treatment, and had a component of youth sports.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies report on this (Aninanya et al 2015;. While this could be due to the way provider service quality is measured, such as by asking adolescents their opinion on the services, or whether they had used services as proxies to directly measuring provider behaviour or service quality, which would then be coded into attitudes, self-efficacy and empowerment, very few of the studies even do this.…”
Section: Gaps In Impact Evaluationmentioning
confidence: 99%